Effect of providing at-home opioid disposal kits at discharge after an orthopaedic surgery - Daniel Lee; M Kit Delgado; Zarina Ali; Anish Agarwal; Eric Shan; Ruiying Xiong; Michael Katzman (BMJ Open Quality)
Prescription opioids after surgery may pose a risk if left unused. However, prescribers rely on their best judgement in determining how much their patients need, often resulting in over-prescription of these medications. Opioid disposal is a strategy to reduce the risk of persistent use or misuse of opioids. At-home disposal kits allow patients to safely dispose of leftover opioids. In this study, we assess the impact of opioid disposal kits on disposal rates after orthopedic surgery. In a difference-in-differences study of 1,321 eligible patients, disposal kits were associated with a 10.6 percentage point increase (95% CI: -3.5% to 24.7%) in disposal rates as well as a 10.5 percentage point increase (95% CI: 0.2% to 20.9%) in the fraction of opioids disposed. We build on prior research and identify that providing surgery patients with an opioid disposal kit at the time of discharge increases their self-disposal rates.